Clinical Supervision as a Strategy to Enhance Teacher Professionalism: A Qualitative Study at SDN 1 Kalipang, Rembang - Muhimatul Lailiyah; Titik Haryati; Sumarno (Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2025)
This study aims to describe and analyze the implementation of clinical supervision as a strategy to enhance teacher professionalism at Kalipang Elementary School, Rembang. A qualitative approach with a case study method was employed. Data were collected through in-depth interviews, observations, and document analysis. The research subjects included the school principal and teachers involved in the supervision process. The findings reveal that clinical supervision was systematically carried out through stages of planning, classroom observation, and reflection. This approach fostered professional communication between the principal and teachers, and encouraged improvements in pedagogical competence and teacher performance in the learning process. Teachers felt more valued, motivated to grow, and open to feedback. Clinical supervision also created a collaborative work environment and supported a culture of continuous learning. This study recommends the consistent implementation of clinical supervision as a strategic effort to improve teacher professionalism and the quality of education in elementary schools.